The relationship between mindfulness and childhood trauma with suicide: The mediating role of cognitive bias - Tabatabaee, Seyed Mosa; Abdolahi, Mohammadamin; Matvaei, Reza; Khalili, Parniyan (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2024)
The purpose of this study is to investigate the relationship between mindfulness, childhood trauma, and suicide, specifically focusing on the mediating role of cognitive bias. Suicide is a pressing issue that poses a significant threat to public health in society, and understanding the factors that contribute to it is crucial. The research design employed in this study is a correlation-based structural equation model. A total of 370 students from the second level of secondary school in Iran city were selected as participants using an available sampling method during the academic year of 2023. To gather data, several questionnaires were utilized, including the Kentucky Mindfulness Questionnaire, Bernstein et al.'s Childhood Trauma Questionnaire (1994), Hammachi and Ozturk's Cognitive Bias Questionnaire (2004), and the Multi-attitude Suicidal Tendency Questionnaire (MAST). Data analysis was conducted using SPSS-23 and Amos software, encompassing both descriptive and inferential levels. The findings of this research revealed several significant relationships. Firstly, there is a positive and significant direct path from childhood trauma to cognitive bias. Secondly, mindfulness has a negative and significant direct path to cognitive bias. Thirdly, childhood trauma has a direct and significant path to suicide. Additionally, cognitive bias has a positive and significant path to suicidality, while mindfulness has a negative and significant path to suicide. Moreover, there are positive and significant indirect paths from suicide to childhood trauma and negative and significant indirect paths from suicide to mindfulness. In conclusion, this study highlights the importance of mindfulness and cognitive bias as variables related to adolescent suicide. Adolescents who have experienced childhood trauma are more likely to consider suicide as a solution when faced with life problems. These findings emphasize the need for interventions and support systems that address mindfulness, cognitive bias, and childhood trauma to prevent and mitigate the risk of suicide among adolescents.